(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study examines the integration of visual and performing arts into multilingual English language classrooms as an innovative pedagogical strategy to enhance linguistic proficiency and foster cultural competence. Traditional language instruction frequently prioritizes grammatical accuracy and vocabulary acquisition while underutilizing the potential of creative expression in facilitating deeper cognitive and affective engagement with language.